How the digital age has changed the corporate communication world: the case of Digital Marketing in the Fashion Business - Medina, Irene Garcia; Pereira Correia, Pedro Alvaro; Amores, Leonor Alberola (IROCAMM - International Review Of Communication And Marketing Mix, 2019)
Digital Marketing have revolutionized the way companies communicate and interact with their publics, in particularly in the Fashion Business. The use of digital communication on a daily is increasingly intense, which leads companies to work the digital business strategy around the objectives, as well as incorporating digital methods into the objectives. According to Hamel, “The advantage of the competitiveness comes from a technological introduction and the constant adaptation along the time to the technological evolution inserted in the strategy of the organization.” This research is a qualitative analysis to understand what are the digital factors that contribute to sustainable competitive advantages of organizations which can support strategic and future actions.